2012
DOI: 10.1073/pnas.1207728109
|View full text |Cite
|
Sign up to set email alerts
|

Two-year survey comparing earthquake activity and injection-well locations in the Barnett Shale, Texas

Abstract: , temporary seismographs deployed under the EarthScope USArray program were situated on a 70-km grid covering the Barnett Shale in Texas, recording data that allowed sensing and locating regional earthquakes with magnitudes 1.5 and larger. I analyzed these data and located 67 earthquakes, more than eight times as many as reported by the National Earthquake Information Center. All 24 of the most reliably located epicenters occurred in eight groups within 3.2 km of one or more injection wells. These included wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
169
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(173 citation statements)
references
References 13 publications
3
169
0
1
Order By: Relevance
“…In the case of the nearby earthquakes at DFW airport, a plausible linkage was found between the disposal of the wastewater and the subsequent earthquakes in the region (Frohlich et al, 2011). A more comprehensive study of local seismicity throughout the Fort Worth basin (Frohlich, 2012) using USArray data to detect and locate events across the basin concludes that there may be a number of locations where small earthquakes are occurring near wastewater injectors. As a result of these previous calculated from source spectra and Lg magnitudes, as calibrated from USGS reports and the pseudomagnitude scale in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the nearby earthquakes at DFW airport, a plausible linkage was found between the disposal of the wastewater and the subsequent earthquakes in the region (Frohlich et al, 2011). A more comprehensive study of local seismicity throughout the Fort Worth basin (Frohlich, 2012) using USArray data to detect and locate events across the basin concludes that there may be a number of locations where small earthquakes are occurring near wastewater injectors. As a result of these previous calculated from source spectra and Lg magnitudes, as calibrated from USGS reports and the pseudomagnitude scale in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of recent seismicity in the Fort Worth basin have identified numerous small earthquakes occurring in close association with injection wells. The survey in Frohlich (2012) of 67 small earthquakes in the Fort Worth basin from 2009 to 2012 found that all the most reliably located events occurred in eight groups each situated within 3.2 km of active injection wells. During the study period, other seismic events ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The potential constraints from environmental issues are not included. Taking shale gas as an example, extracting shale gas may result in many environmental problems, including methane emissions, water use, water pollution, and induced earthquakes (Howarth and Ingraffea 2011;Entrekin et al 2011;Frohlich 2012). Among these, water issues may be the most significant constraining factor for China shale's gas development.…”
Section: Non-conventional Gas Productionmentioning
confidence: 99%
“…It is also key for the civil engineering, mining, and energy industries, covering topics as diverse as hydraulic fracturing, rock stability, and fluid circulation (Simonson et al, 1978;Van Eekelen, 1982;Warpinski et al, 1985;Hopkins, 1997;King, 2010;Fisher and Warpinski, 2011;Davies et al, 2012). Furthermore, it is important for determining the likelihood of felt seismicity due to human activities, for instance, because of hydraulic fracturing or saltwater disposal (Frohlich, 2012;Ellsworth, 2013;Weingarten et al, 2015;Atkinson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%